The Influence of Brand Trust on Perceived Value and Purchase Intention with Brand Preference Avoskin - Kurniawan, Risfan Nova; Henny Welsa; Lusia Tria Hatmanti Hutami (Journal of Economy, Accounting and Management Science (JEAMS), 2026)
This research aims to analyze the effect of purchase intention on AVOSKIN products which influences brand trust and perceived value toward AVOSKIN. The population in this research is AVOSKIN customers who have made at least one purchase. The object of this research is AVOSKIN customers in Yogyakarta in 2024. The sample is purposive and obtained from 100 respondents, which were then analyzed using multiple linear regression and the Sobel test. The sampling technique was conducted by distributing questionnaires using Google Forms through WhatsApp. The author conducted a study on the AVOSKIN brand as the object of this research. The purposes of this research are (1) brand trust influences brand preference, (2) perceived value influences brand preference, (3) brand trust influences purchase intention, (4) perceived value influences purchase intention, and (5) brand preference influences purchase intention. The results of the research show that brand trust has a positive and significant effect on brand preference. Perceived value has a positive and significant effect on brand preference, and functional value has a positive and significant effect on customer satisfaction. Brand preference has a positive and significant effect on purchase intention, but brand trust does not have a positive and significant effect on purchase intention and perceived value does not have a positive and significant effect on purchase intention.